The pharmacognosy investigation of associated coumarins Lupinus luteus L - Grechana, O. V.; Saliy, O. O.; Serbin, A. G.; Fukleva, L. A.; Гречана, Олена Володимирівна; Салій, О. О.; Сербін, А. Г.; Фуклева, Лариса Анатоліївна (My University, 2019)
In this paper we focuses on the issue of pharmacognostical study of plants is widely used in animal breeding, is the active substance in the manufacture of dietary supplements - the yellow lupine (Fabaceae). Harvested grass were analyzed after acid hydrolysis
Keywords: Pharmacognosy; Investigation; Coumarins; Lupinus